The Influence of Counseling of Food Management of Breastfeeding Companion (MP-ASI) on Mother Against Action of Diarrhea Prevention in Infants at RSUD. Dr. H. Moch Ansari Saleh Banjarmasin. - Dewi Pusparani Sinambela; Ramalida Daulai; Khalifatunnisa Fitria (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Introduction: Diarrhea is included in 10 diseases that often cause extraordinary events, in developing countries such as the state of Indonesia. Incidence of diarrhea in infants in hospitals. Dr. H. Moch Ansari Saleh Alexandri room in 2016 number of 242 cases of infants. Diarrhea can be an acute and dangerous illness it often results in death when it is too late handled. One of the factors of counseling is one of theefforts to conduct guidance, for the prevention of diarrhea, especially in the management of complementary foods of breast milk.Objective: The influence of counseling management of complementary foods of mother's milk (MP-ASI)on the prevention of diarrhea in infantsMethod: Pre Experiment Design with One group Pretest – Posttest design. Sample in this study using Purposive sampling technique, that is as many as 20 mothers who have baby 6-12 month. Data analysis technique using t test.Results: Test paired sample t test on post-test after giving leaflet with leaflet (p value = 0,000) and diarrhea prevention action on Pretest before giving leaflet counseling (p value = 0,000). The test result of independent sample t test obtained value (p value = 0,027) so it can be concluded that there is influence between VariableConclusion: Counseling can be one way to increase the prevention of diarrhea by maximizing the role of health worker or apprentices and It is expected that mothers who have babies with counseling can improve preventive measures of diarrhea.Keywords: Counseling, Food Management of Breastfeeding Companion, Diarrhea, Breastfeeding mother